Clinical Profile of Dengue Patients Admitted during the 2023 Bangladesh Dengue Outbreak (East West Medical College Journal, 2026)
Background: Dengue virus infection, a major public health concern in tropical regions, can cause a spectrum of illness. Bangladesh experiences seasonal dengue outbreaks, with the 2023 outbreak being the worst in recent years. DENV-2 predominance, low population immunity, and overwhelmed healthcare systems likely contributed to the severity. This study investigates the clinical profile of patients admitted during the 2023 outbreak peak (April-July) at a tertiary care hospital in Dhaka, Bangladesh.Methods: A retrospective analysis of medical records from dengue-confirmed patients (NS1 Ag, IgM, or IgG) admitted during the 2023 outbreak peak (April-July) at Shaheed Monsur Ali Medical College Hospital, Dhaka, Bangladesh, was conducted. A standardized data collection form captured demographics, clinical symptoms, vital signs, laboratory findings, and treatment details. Disease severity was classified using WHO guidelines. Descriptive statistics and frequency calculations summarized the data.Results: This study analysis included 174 dengue patients admitted during the 2023 outbreak peak. The mean age was 36.44 years (range: 15-67 years) with a male predominance (55.7%). Fever was universal, followed by frequent headaches (93.1%) and myalgia (77.6%). Thrombocytopenia (78.7%) and elevated hematocrit (56.3%) were common laboratory findings. Fluid resuscitation with crystalloids and paracetamol for fever management were used for all patients. Blood transfusions were administered in only 14.9% due to severe thrombocytopenia or bleeding.Conclusion: This study describes the clinical profile of the dengue patients admitted during the 2023 Bangladesh outbreak. Findings align with prior research on dengue presentations and management. Further studies are needed to explore the impact of factors like serotype and disease severity. The study highlights the importance of maintaining a high index of suspicion for dengue, particularly during outbreaks, to facilitate timely diagnosis and optimal management.EWMCJ Vol. 14, No. 1, January 2026: 61-66